An Adsorbate Discriminatory Gate Effect in a Flexible Porous Coordination Polymer for Selective Adsorption of CO2 over C2H2 - Foo, Maw Lin; Matsuda, Ryotaro; Hijikata, Yuh; Krishna, Rajamani; Sato, Hiroshi; Horike, Satoshi; Hori, Akihiro; Duan, Jingui; Sato, Yohei; Kubota, Yoshiki; Takata, Masaki; Kitagawa, Susumu (Journal of the American Chemical Society, 2016)
The adsorptive separation of C2H2 and CO2 via porous materials is nontrivial due to the close similarities of their boiling points and kinetic diameters. In this work, we describe a new flexible porous coordination polymer (PCP) [Mn(bdc)(dpe)] (H2bdc = 1,4-benzenedicarboxylic acid, dpe = 1,2-di(4-pyridyl)ethylene) having zero-dimensional pores, which shows an adsorbate discriminatory gate effect. The compound shows gate opening type abrupt adsorption for C2H2 but not for CO2, leading to an appreciable selective adsorption of CO2 over C2H2 at near ambient temperature (273 K). The origin of this unique selectivity, as unveiled by in situ adsorption-X-ray diffraction experiments and density functional theory calculations, is due to vastly different orientations between the phenylene ring of bdc and each gas in the nanopores. The structural change by photochemical transformation of this PCP via [2 + 2] photodimerization leads to the removal of inverse CO2/C2H2 selectivity, verifying the mechanism of the guest discriminatory gate effect.